Snake-like soft robot using 2-chambers actuator - Abdulrab, Hakim Q.A.; Mohd Nordin, Ili Najaa Aimi; Muhammad Razif, Muhammad Rusydi; Faudzi, Ahmad Athif (Penerbit UTM Press, 2018)
Many researchers have been working on snake-like robots due to their flexibility, safety and dexterity. Traditional robots have rigid underlying structures that limit their ability to interact with their environment. In this work, soft robot is developed using three links of the flexible soft actuator connected by rubber joints. The actuators are fabricated using silicon Silastic P-1 where each actuator link consists of two semi-circular chambers and are reinforced with fibers. Fabrication process from CAD design, mold fabrication and validation with simulation and experiment is presented. The fabricated actuators can bend at 27.5o with maximum pressure of 180 kPa.